Broadband-gap perovskite solar cell and preparation method thereof

By adopting a double-layer passivation process in a wide-bandgap perovskite solar cell, a double passivation layer composed of poly(2-ethyl-2-oxazoline) and phenethylamine salt is solved, and the problem that the existing passivation agent cannot reduce the open circuit voltage loss is achieved, and the effect of improving the open circuit voltage and photoelectric conversion efficiency is achieved.

CN120166843APending Publication Date: 2025-06-17MIANYANG XINHAO NEW ENERGY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510555501.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-06-17

AI Technical Summary

Technical Problem

Existing solar cell passivators cannot effectively meet the need for wide-bandgap perovskite solar cells to reduce open circuit voltage losses.

Method used

A double-layer passivation process is adopted, and a double passivation layer composed of poly(2-ethyl-2-oxazoline) and phenethylamine salt (such as n-R phenethylamine X) is used to adjust the surface energy level of the perovskite to reduce the open circuit voltage loss through intermolecular force and surface dipole effect.

Benefits of technology

It effectively improves the open circuit voltage and photoelectric conversion efficiency of wide-bandgap perovskite solar cells, and solves the problem that existing passivators cannot meet the needs of wide-bandgap perovskites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120166843A_ABST
    Figure CN120166843A_ABST
Patent Text Reader

Abstract

The invention discloses a wide-band-gap perovskite solar cell and a preparation method thereof, and relates to the technical field of solar cells, and the wide-band-gap perovskite solar cell comprises a wide-band-gap perovskite layer and double passivation layers. The double passivation layer is located above the wide-band-gap perovskite layer; and the double passivation layer comprises poly (2-ethyl-2-oxazoline) and a phenylethylamine salt. The preparation method of the double passivation layers comprises the following steps: coating the surface of a perovskite thin film with a chlorobenzene solution containing poly (2-ethyl-2-oxazoline), and then carrying out annealing treatment; and after annealing, coating an isopropanol solution containing phenylethylamine salt. And a double-layer passivation process is adopted, so that the purposes of fully reducing interface recombination and improving the open-circuit voltage and photoelectric conversion efficiency of the wide-band-gap device are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and particularly relates to a wide-bandgap perovskite solar cell and a preparation method thereof. Background Art

[0002] Perovskite solar cells are a type of solar cell technology that uses perovskite materials as the light absorption layer. Such cells have attracted much attention due to their high photoelectric conversion efficiency, relatively low manufacturing cost, and potential application flexibility. Perovskite solar cells are light, flexible, and transparent, and can be arranged on various different surfaces such as roofs and glass, and can even be set on the outer walls of buildings, etc., greatly increasing the proportion of renewable energy. Perovskite is a type of mineral with a crystalline structure, and in solar cells, artificially synthesized perovskite materials exhibit excellent photoelectric conversion performance due to their unique properties, such as high light absorption rate and adjustable bandgap.

[0003] Surface passivation of perovskite solar cells refers to the process of eliminating defects and regulating energy levels on the surface of the perovskite thin film through physical or chemical treatment. This process can effectively reduce non-radiative recombination and improve the open-circuit voltage and photoelectric conversion efficiency of solar cells. When passivating the surface of solar cells, a solar cell passivation agent is required. A solar cell passivation agent is a material used to improve the performance of solar cells, and its main function is to improve the photoelectric conversion efficiency of the cell by reducing the defects on the cell surface. The passivation agent can effectively reduce the leakage current at the edge of the cell, thereby improving the overall efficiency and stability of the cell.

[0004] Currently, commonly used passivation agents for perovskite solar cells are phenethylamine iodide (PEAI) and octylamine iodide (OAI), but the current solar cell passivation agents are only applicable to perovskites with a general bandgap and cannot effectively meet the demand of wide-bandgap perovskites for reducing open-circuit voltage loss. Summary of the Invention

[0005] Based on the problem that the current solar cell passivation agents are only applicable to perovskites with a general bandgap and cannot effectively meet the demand of wide-bandgap perovskites for reducing open-circuit voltage loss, the purpose of the present invention is to provide a wide-bandgap perovskite solar cell and a preparation method thereof, which improve the open-circuit voltage and conversion efficiency of perovskite solar cells.

[0006] The present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present application provides a wide-bandgap perovskite solar cell, including a wide-bandgap perovskite layer and a double passivation layer;

[0008] The double passivation layer is located above the wide-bandgap perovskite layer;

[0009] The double passivation layer includes poly(2-ethyl-2-oxazoline) and phenylamine salt.

[0010] Furthermore, the structure of the phenylamine salt is n-R-phenylethylamine X, where n = 1, 2 or 3, R is F, Cl, Br, CH3 or OCH3, and X is I, Br or Cl.

[0011] In the passivator of the present invention, poly(2-ethyl-2-oxazoline) (PEOXA) is a polymer with moderate intermolecular forces, which can effectively clean the perovskite surface without affecting its lattice structure. At the same time, its electron-donating group can passivate the uncoordinated Pb 2+ defects. In addition, phenylamine bromide (PEABr) can form a surface dipole without directly contacting the perovskite surface, thereby adjusting the perovskite surface energy level and achieving better energy level matching with the hole transport layer. Therefore, the combination of poly(2-ethyl-2-oxazoline) (PEOXA) and phenylamine bromide (PEABr) realizes double-layer passivation, which reduces the open-circuit voltage loss of the wide-bandgap perovskite and improves the open-circuit voltage and conversion efficiency of the perovskite solar cell.

[0012] Furthermore, from bottom to top, it sequentially includes a conductive glass substrate, an electron transport layer, a wide-bandgap perovskite layer, a double passivation layer, a hole transport layer, and a metal electrode.

[0013] Furthermore, the conductive glass substrate includes at least one of FTO glass and ITO glass; the electron transport layer includes at least one of SnO2, TiO2, and ZnO; the wide-bandgap perovskite layer has a composition of Cs x FA 1-x-y MA y Pb(I 1-z- w Br z Cl w )3, where 0.1 ≤ x ≤ 0.4, 0.02 ≤ y ≤ 0.05, 0.1 ≤ z ≤ 0.4, 0.02 ≤ w ≤ 0.05, and the bandgap of the wide-bandgap perovskite layer is 1.65 - 1.90 eV; the hole transport layer includes at least one of Spiro-OMeTAD, PTAA, and NiO x ; and the metal electrode includes at least one of gold, silver, copper, and aluminum.

[0014] In a second aspect, the present application provides a method for preparing the above-mentioned wide-bandgap perovskite solar cell, including the following steps:

[0015] Deposit a double passivation layer on the surface of the wide-bandgap perovskite layer.

[0016] Furthermore, the method for depositing the double passivation layer on the surface of the wide-bandgap perovskite layer includes:

[0017] A chlorobenzene solution containing poly(2-ethyl-2-oxazoline) is coated on the surface of the wide-bandgap perovskite layer, and then annealing treatment is carried out;

[0018] After annealing, an isopropanol solution containing phenylammonium salt is coated again.

[0019] The passivation method of the perovskite solar cell of the present invention adopts a double-layer passivation process to fully reduce interfacial recombination and improve the open-circuit voltage of the device, realize the reduction of the open-circuit voltage loss of the wide-bandgap perovskite, and improve the open-circuit voltage and conversion efficiency of the perovskite solar cell.

[0020] Further, the concentration of the poly(2-ethyl-2-oxazoline) is 0.01 mg / mL to 1 mg / mL, and the concentration of the phenylammonium salt is 0.1 mg / mL to 10 mg / mL.

[0021] Further, the coating method includes a spin coating method. The rotation speed during spin coating the chlorobenzene solution containing poly(2-ethyl-2-oxazoline) is 1000 rpm to 4000 rpm; the rotation speed during spin coating the isopropanol solution containing phenylammonium salt is 4000 rpm to 6000 rpm.

[0022] Further, the temperature during the annealing treatment is 60 °C to 120 °C.

[0023] Further, the time of the annealing treatment is 0 to 15 min.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0025] In the present invention, poly(2-ethyl-2-oxazoline) (PEOXA) in the double-layer passivation layer of the wide-bandgap perovskite solar cell is a polymer with moderate intermolecular forces, which can effectively clean the perovskite surface without affecting its lattice structure. At the same time, its electron-donating group can be used to passivate the uncoordinated Pb 2+ defects. In addition, phenylammonium bromide (PEABr) can form a surface dipole without directly contacting the perovskite surface, thereby adjusting the perovskite surface energy level and achieving better energy level matching with the hole transport layer. Therefore, the combination of poly(2-ethyl-2-oxazoline) (PEOXA) and phenylammonium bromide (PEABr) realizes double-layer passivation, which plays a role in reducing the open-circuit voltage loss of the wide-bandgap perovskite and improves the open-circuit voltage and conversion efficiency of the perovskite solar cell. Brief Description of the Drawings

[0026] To more clearly illustrate the technical solutions in the present application, the following will briefly introduce the accompanying drawings required for the description of the embodiments. Obviously, the accompanying drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, without creative efforts, other accompanying drawings can be obtained based on these drawings.

[0027] Figure 1 It is a comparison chart of the conversion efficiency of the perovskite solar cells prepared in Example 1 of the present invention and Comparative Examples 1-3;

[0028] Figure 2 It is a comparison chart of the open circuit voltage of the perovskite solar cells prepared in Example 1 of the present invention and Comparative Examples 1-3.

[0029] Figure 3 It is a comparison chart of the J-V curves of the perovskite solar cells prepared in Example 1 of the present invention and Comparative Examples 1-3. Detailed implementation manners

[0030] To make the objectives, technical solutions and advantages of the present invention more clearly understood, the following further details the present invention in conjunction with embodiments. The illustrative embodiments and descriptions thereof of the present invention are only used to explain the present invention and are not intended to limit the present invention.

[0031] In the following description, numerous specific details are set forth in order to provide a thorough understanding of the present invention. However, it is obvious to those of ordinary skill in the art that the present invention does not have to be practiced with these specific details. In other embodiments, well-known materials or methods are not specifically described in order to avoid obscuring the present invention.

[0032] Throughout the specification, the reference to "one embodiment", "an embodiment", "one example" or "an example" means that the specific features, structures or characteristics described in connection with that embodiment or example are included in at least one embodiment of the present invention. Thus, the phrases "one embodiment", "an embodiment", "one example" or "an example" appearing throughout the specification do not necessarily all refer to the same embodiment or example. In addition, the specific features, structures or characteristics can be combined in any suitable combination and / or sub-combination in one or more embodiments or examples. The term "and / or" used herein includes any and all combinations of one or more of the associated listed items. In addition, without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples.

[0033] The "ranges" disclosed in this application are defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The ranges defined in this way can include or exclude the end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, ranges of 60-110 and 80-120 are also contemplated. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4, and 5 are listed, then the following ranges are all contemplated: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "a-b" represents an abbreviated representation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been fully listed herein, and "0-5" is only an abbreviated representation of these numerical combinations. Additionally, when stating that a certain parameter is an integer ≥2, it is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0034] Example 1

[0035] This example provides a method for preparing a wide-bandgap perovskite solar cell, which is carried out according to the following steps:

[0036] S1. Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it into a glass box, and sequentially add a conductive glass cleaning solution (diluted with deionized water to 2%), deionized water, acetone, and isopropanol, and ultrasonically clean for 15 min. After the cleaning is completed, dry the conductive glass with a nitrogen gas gun and treat it with oxygen plasma for 15 min.

[0037] S2. Dilute a commercially available tin oxide colloid dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat for 30 s at a rotation speed of 4000 rpm. After the spin-coating is completed, anneal it on a hot plate at 150 °C for 30 min. After the annealing is completed, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0038] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15) 3 + 5 mol% MACl + 3 mol% PbCl2, the required materials and masses are as follows: Methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it onto the treated tin oxide substrate, and spin-coat it at 5000 rpm for 20 s. 5 s before the end of the spin-coating process, quickly drop 100 μL of chlorobenzene onto the center of the film. After the spin-coating process is completed, anneal it on a hot plate at 100 °C for 30 min.

[0039] S4. Dissolve 0.05 mg / mL of poly(2-ethyl-2-oxazoline) (PEOXA) in chlorobenzene to form a solution, and spin-coat this solution onto the surface of the perovskite film at 2000 rpm. After annealing treatment at 100 °C for 5 min, then spin-coat a 2 mg / mL solution of phenethylamine bromide (PEABr) in isopropanol onto the surface of the perovskite film at 5000 rpm to achieve two-step passivation.

[0040] S5. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, and add 28.8 μL of tBP and 35 μL of a Li-TFSI solution (260 mg / ml dissolved in acetonitrile). Take 60 μL and drop it onto the passivated perovskite surface, and spin-coat it at 4000 rpm for 30 s.

[0041] S6. Deposit 70 nm thick gold as the electrode by vacuum thermal evaporation to obtain a perovskite solar electrode.

[0042] Example 2

[0043] This example provides a method for preparing a wide-bandgap perovskite solar cell. Different from Example 1, the concentration of poly(2-ethyl-2-oxazoline) used in step S4 of this example is 0.02 mg / mL, and other processes are the same as those in Example 1. The steps are as follows:

[0044] S1. Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it into a glass box, and sequentially add a conductive glass cleaning solution (diluted with deionized water to 2%), deionized water, acetone, and isopropanol, and ultrasonicate for 15 min. After the cleaning is completed, dry the conductive glass with a nitrogen air gun and treat it with oxygen plasma for 15 min.

[0045] S2. Dilute the commercial tin oxide colloidal dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat it at a speed of 4000 rpm for 30 s. After the spin-coating is completed, anneal it on a hot plate at 150 °C for 30 min. After the annealing is completed, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0046] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 + 5 mol% MACl + 3 mol% PbCl2. The required materials and masses are as follows: methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), and lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it on the treated tin oxide substrate, and spin-coat it at a speed of 5000 rpm for 20 s. 5 s before the end of the spin-coating program, quickly drop 100 μL of chlorobenzene onto the center of the film. After the spin-coating program is completed, anneal it on a hot plate at 100 °C for 30 min.

[0047] S4. Dissolve 0.02 mg / mL of poly(2-ethyl-2-oxazoline) (PEOXA) in chlorobenzene to form a solution, and spin-coat this solution on the surface of the perovskite film at 2000 rpm. After annealing treatment at 100 °C for 5 min, then spin-coat a 2 mg / mL solution of phenethylamine bromide (PEABr) in isopropanol on the surface of the perovskite film to achieve two-step passivation.

[0048] S5. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of a Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it on the passivated perovskite surface, and spin-coat it at 4000 rpm for 30 s.

[0049] S6. Deposit 70 nm thick gold as the electrode by vacuum thermal evaporation to obtain a perovskite solar electrode.

[0050] Example 3

[0051] This example provides a preparation method for a wide-bandgap perovskite solar cell. Different from Example 1, the concentration of poly(2-ethyl-2-oxazoline) used in step S4 of this example is 1 mg / mL, and other processes are the same as those in Example 1. The steps are as follows:

[0052] S1. Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it into a glass box, and sequentially add a conductive glass cleaning solution (diluted with deionized water to 2%), deionized water, acetone, and isopropanol, and ultrasonicate for 15 min. After cleaning, dry the conductive glass with a nitrogen gas gun and treat it with oxygen plasma for 15 min.

[0053] S2. Dilute a commercial tin oxide colloidal dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat for 30 s at a rotation speed of 4000 rpm. After spin-coating, place it on a hot plate and anneal at 150 °C for 30 min. After annealing, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0054] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 + 5 mol% MACl + 3 mol% PbCl2. The required materials and masses are as follows: methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), and lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it on the treated tin oxide substrate, and spin-coat for 20 s at a rotation speed of 5000 rpm. 5 s before the end of the spin-coating process, quickly drop 100 μL of chlorobenzene on the center of the film. After the spin-coating process is completed, place it on a hot plate and anneal at 100 °C for 30 min.

[0055] S4. Dissolve 1 mg / mL poly(2-ethyl-2-oxazoline) (PEOXA) in chlorobenzene to form a solution, and spin-coat this solution on the surface of the perovskite film at 2000 rpm. After annealing treatment at 100 °C for 5 min, then spin-coat a 2 mg / mL phenethylamine bromide (PEABr) isopropanol solution on the surface of the perovskite film at 5000 rpm to achieve two-step passivation.

[0056] S5. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of a Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it on the passivated perovskite surface, and spin-coat for 30 s at 4000 rpm.

[0057] S6. Deposit 70 nm thick gold as an electrode by vacuum thermal evaporation to obtain a perovskite solar electrode.

[0058] Example 4

[0059] This embodiment provides a method for preparing a wide-bandgap perovskite solar cell. Different from Embodiment 1, the concentration of phenethylamine bromide used in step S4 of this embodiment is 0.5 mg / mL, and other processes are the same as those in Embodiment 1. The steps are as follows:

[0060] S1. Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it into a glass box, and sequentially add a conductive glass cleaning solution (diluted with deionized water to 2%), deionized water, acetone, and isopropanol, and ultrasonically clean for 15 min. After the cleaning is completed, dry the conductive glass with a nitrogen air gun and treat it with oxygen plasma for 15 min.

[0061] S2. Dilute a commercial tin oxide colloid dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat for 30 s at a rotation speed of 4000 rpm. After the spin-coating is completed, anneal it on a hot plate at 150 °C for 30 min. After the annealing is completed, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0062] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 + 5 mol% MACl + 3 mol% PbCl2. The required materials and masses are as follows: methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), and lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it on the treated tin oxide substrate, and spin-coat for 20 s at a rotation speed of 5000 rpm. 5 s before the end of the spin-coating program, quickly drop 100 μL of chlorobenzene on the center of the film. After the spin-coating program is completed, anneal it on a hot plate at 100 °C for 30 min.

[0063] S4. Dissolve 0.05 mg / mL poly(2-ethyl-2-oxazoline) (PEOXA) in chlorobenzene to form a solution, and spin-coat this solution on the surface of the perovskite film at 2000 rpm. After annealing treatment at 100 °C for 5 min, then spin-coat a 0.5 mg / mL phenethylamine bromide (PEABr) isopropanol solution on the surface of the perovskite film at 5000 rpm to achieve two-step passivation.

[0064] S5. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it on the passivated perovskite surface, and spin-coat it at 4000 rpm for 30 s.

[0065] S6. Deposit 70 nm thick gold as the electrode by vacuum thermal evaporation to obtain a perovskite solar electrode.

[0066] Example 5

[0067] This example provides a method for preparing a wide-bandgap perovskite solar cell. Different from Example 1, the concentration of phenethylamine bromide used in step S4 of this example is 5 mg / mL, and other processes are the same as those in Example 1. The steps are as follows:

[0068] S1. Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it into a glass box, and sequentially add a conductive glass cleaning solution (diluted with deionized water to 2%), deionized water, acetone, and isopropanol, and ultrasonicate for 15 min. After the cleaning is completed, dry the conductive glass with a nitrogen air gun and treat it with oxygen plasma for 15 min.

[0069] S2. Dilute a commercial tin oxide colloidal dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat it at a speed of 4000 rpm for 30 s. After the spin-coating is completed, place it on a hot plate and anneal it at 150 °C for 30 min. After the annealing is completed, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0070] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 + 5 mol% MACl + 3 mol% PbCl2. The required materials and masses are as follows: methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), and lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it on the treated tin oxide substrate, and spin-coat it at a speed of 5000 rpm for 20 s. 5 s before the end of the spin-coating program, quickly drop 100 μL of chlorobenzene on the center of the film. After the spin-coating program is completed, place it on a hot plate and anneal it at 100 °C for 30 min.

[0071] S4. Dissolve 0.05 mg / mL of poly(2-ethyl-2-oxazoline) (PEOXA) in chlorobenzene to form a solution, and spin-coat this solution on the surface of the perovskite film at 2000 rpm. After annealing at 100 °C for 5 min, spin-coat a 5 mg / mL solution of phenethylamine bromide (PEABr) in isopropanol on the surface of the perovskite film at 5000 rpm to achieve two-step passivation.

[0072] S5. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of a Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it on the passivated perovskite surface, and spin-coat at 4000 rpm for 30 s.

[0073] S6. Deposit 70 nm thick gold as the electrode by vacuum thermal evaporation to obtain a perovskite solar electrode.

[0074] Example 6

[0075] This example provides a method for preparing a wide-bandgap perovskite solar cell. Different from Example 1, in step S4 of this example, phenethylamine iodide is used instead of phenethylamine bromide. Other processes are the same as those in Example 1 and are carried out according to the following steps:

[0076] S1. Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it into a glass box, and sequentially add a conductive glass cleaning solution (diluted with deionized water to 2%), deionized water, acetone, and isopropanol, and ultrasonicate for 15 min. After cleaning, dry the conductive glass with a nitrogen air gun and treat it with oxygen plasma for 15 min.

[0077] S2. Dilute a commercial tin oxide colloid dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat at a rotation speed of 4000 rpm for 30 s. After spin-coating, place it on a hot plate and anneal at 150 °C for 30 min. After annealing, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0078] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15) 3 + 5 mol% MACl + 3 mol% PbCl2, the required materials and masses are as follows: methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it onto the treated tin oxide substrate, and spin-coat it at 5000 rpm for 20 s. 5 s before the end of the spin-coating process, quickly drop 100 μL of chlorobenzene onto the center of the film. After the spin-coating process is completed, place it on a hot plate at 100 °C and anneal for 30 min.

[0079] S4. Dissolve 0.05 mg / mL of poly(2-ethyl-2-oxazoline) (PEOXA) in chlorobenzene to form a solution, and spin-coat this solution onto the surface of the perovskite film at 2000 rpm. After annealing at 100 °C for 5 min, then spin-coat a 2 mg / mL phenethylamine iodide (PEAI) isopropanol solution onto the surface of the perovskite film at 5000 rpm to achieve two-step passivation.

[0080] S5. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of a Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it onto the passivated perovskite surface, and spin-coat it at 4000 rpm for 30 s.

[0081] S6. Deposit 70 nm thick gold as the electrode by vacuum thermal evaporation to obtain a perovskite solar electrode.

[0082] Example 7

[0083] This example provides a method for preparing a wide-bandgap perovskite solar cell. Different from Example 1, in step S4 of this example, 2-bromo-phenethylamine bromide is used instead of phenethylamine bromide. Other processes are the same as in Example 1 and are carried out according to the following steps:

[0084] S1. Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it into a glass box, and sequentially add a conductive glass cleaning solution (diluted to 2% with deionized water), deionized water, acetone, and isopropanol, and ultrasonicate for 15 min. After the cleaning is completed, dry the conductive glass with a nitrogen air gun and treat it with oxygen plasma for 15 min.

[0085] S2. Dilute the commercial tin oxide colloidal dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat it at a speed of 4000 rpm for 30 s. After spin-coating, anneal it on a hot plate at 150 °C for 30 min. After annealing, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0086] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 + 5 mol% MACl + 3 mol% PbCl2. The required materials and masses are as follows: methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it on the treated tin oxide substrate, and spin-coat it at a speed of 5000 rpm for 20 s. 5 s before the end of the spin-coating process, quickly drop 100 μL of chlorobenzene on the center of the film. After the spin-coating process is completed, anneal it on a hot plate at 100 °C for 30 min.

[0087] S4. Dissolve 0.05 mg / mL poly(2-ethyl-2-oxazoline) (PEOXA) in chlorobenzene to form a solution, and spin-coat this solution on the surface of the perovskite film at 2000 rpm. After annealing treatment at 100 °C for 5 min, then spin-coat a 2 mg / mL 2-bromoethylamine bromide (2-BrPEABr) isopropanol solution on the surface of the perovskite film at 5000 rpm to achieve two-step passivation.

[0088] S5. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of a Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it on the passivated perovskite surface, and spin-coat it at 4000 rpm for 30 s.

[0089] S6. Deposit 70 nm thick gold as the electrode by vacuum thermal evaporation to obtain a perovskite solar electrode.

[0090] Example 8

[0091] This example provides a preparation method of a wide-bandgap perovskite solar cell. Different from Example 1, in step S4 of this example, 1-methoxyphenethylamine iodide is used, and other processes are the same as those in Example 1. The steps are as follows:

[0092] S1. Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it into a glass box, and sequentially add a conductive glass cleaning solution (diluted with deionized water to 2%), deionized water, acetone, and isopropanol, and ultrasonically clean for 15 min. After the cleaning is completed, dry the conductive glass with a nitrogen gas gun and treat it with oxygen plasma for 15 min.

[0093] S2. Dilute a commercial tin oxide colloidal dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat it at a rotational speed of 4000 rpm for 30 s. After the spin-coating is completed, anneal it on a hot plate at 150 °C for 30 min. After the annealing is completed, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0094] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 + 5 mol% MACl + 3 mol% PbCl2. The required materials and masses are as follows: methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), and lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it on the treated tin oxide substrate, and spin-coat it at a rotational speed of 5000 rpm for 20 s. 5 s before the end of the spin-coating process, quickly drop 100 μL of chlorobenzene on the center of the film. After the spin-coating process is completed, anneal it on a hot plate at 100 °C for 30 min.

[0095] S4. Dissolve 0.05 mg / mL poly(2-ethyl-2-oxazoline) (PEOXA) in chlorobenzene to form a solution, and spin-coat this solution on the surface of the perovskite film at 2000 rpm. After annealing treatment at 100 °C for 5 min, then spin-coat a 2 mg / mL 1-methoxyphenethylamine iodide (1-MeOPEAI) isopropanol solution on the surface of the perovskite film at 5000 rpm to achieve two-step passivation.

[0096] S5. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of a Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it on the passivated perovskite surface, and spin-coat it at 4000 rpm for 30 s.

[0097] S6. Use vacuum thermal evaporation to deposit 70 nm thick gold as the electrode to obtain a perovskite solar electrode.

[0098] Comparative Example 1

[0099] This comparative example provides a method for preparing a perovskite solar cell. Different from Example 1, in step S4 of this comparative example, only a chlorobenzene solution containing poly(2-ethyl-2-oxazoline) was coated, that is, only one layer of passivation was carried out, and other processes were the same as those in Example 1, and the following steps were carried out:

[0100] S1. Place a 2 cm×2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it into a glass box, and sequentially add a conductive glass cleaning solution (diluted with deionized water to 2%), deionized water, acetone, and isopropanol, and ultrasonically clean for 15 min. After the cleaning is completed, dry the conductive glass with a nitrogen gas gun and treat it with oxygen plasma for 15 min.

[0101] S2. Dilute a commercial tin oxide colloidal dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat for 30 s at a rotation speed of 4000 rpm. After the spin-coating is completed, anneal it on a hot plate at 150 °C for 30 min. After the annealing is completed, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0102] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 + 5 mol% MACl + 3 mol% PbCl2. The required materials and masses are as follows: methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), and lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it on the treated tin oxide substrate, and spin-coat for 20 s at a rotation speed of 5000 rpm. 5 s before the end of the spin-coating program, quickly drop 100 μL of chlorobenzene on the center of the film. After the spin-coating program is completed, anneal it on a hot plate at 100 °C for 30 min.

[0103] S4. Dissolve 0.05 mg / mL poly(2-ethyl-2-oxazoline) (PEOXA) in chlorobenzene to form a solution, and spin-coat this solution on the surface of the perovskite film at 2000 rpm.

[0104] S5. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of a Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it on the passivated perovskite surface, and spin-coat for 30 s at 4000 rpm.

[0105] S6. Deposit 70 nm thick gold as the electrode by vacuum thermal evaporation to obtain a perovskite solar electrode.

[0106] Comparative Example 2

[0107] This comparative example provides a method for preparing a perovskite solar cell. Different from Example 1, in step S4 of this comparative example, only an isopropanol solution containing phenethylamine bromide was coated, and only one layer of passivation was carried out. Other processes are the same as those in Example 1, and are carried out according to the following steps:

[0108] S1. Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it into a glass box, and sequentially add a conductive glass cleaning solution (diluted with deionized water to 2%), deionized water, acetone, and isopropanol, and ultrasonically clean for 15 min. After the cleaning is completed, dry the conductive glass with a nitrogen gas gun and treat it with oxygen plasma for 15 min.

[0109] S2. Dilute a commercial tin oxide colloid dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat for 30 s at a rotation speed of 4000 rpm. After the spin-coating is completed, anneal it on a hot plate at 150 °C for 30 min. After the annealing is completed, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0110] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 + 5 mol% MACl + 3 mol% PbCl2. The required materials and masses are as follows: methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), and lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it on the treated tin oxide substrate, and spin-coat for 20 s at a rotation speed of 5000 rpm. 5 s before the end of the spin-coating program, quickly drop 100 μL of chlorobenzene on the center of the film. After the spin-coating program is completed, anneal it on a hot plate at 100 °C for 30 min.

[0111] S4. Spin-coat a 2 mg / mL phenethylamine bromide (PEABr) isopropanol solution on the surface of the perovskite film at 5000 rpm.

[0112] S5. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it on the passivated perovskite surface, and spin-coat it at 4000 rpm for 30 s.

[0113] S6. Deposit 70 nm thick gold as the electrode by vacuum thermal evaporation to obtain a perovskite solar electrode.

[0114] Comparative Example 3

[0115] This comparative example provides a method for preparing a perovskite solar cell. Different from Example 1, this comparative example does not coat a passivation layer, and other processes are the same as those in Example 1, and are carried out according to the following steps:

[0116] S1. Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it in a glass box, and sequentially add a conductive glass cleaning solution (diluted to 2% with deionized water), deionized water, acetone, and isopropanol, and ultrasonically clean for 15 min. After the cleaning is completed, dry the conductive glass with a nitrogen air gun and treat it with oxygen plasma for 15 min.

[0117] S2. Dilute a commercial tin oxide colloid dispersion with deionized water to 2.5 wt%, take 100 μL and drop it on the treated conductive glass substrate, and spin-coat it at a rotation speed of 4000 rpm for 30 s. After the spin-coating is completed, anneal it on a hot plate at 150 °C for 30 min. After the annealing is completed, treat it with oxygen plasma for 2 min and transfer it into a nitrogen glove box.

[0118] S3. The chemical composition of the wide-bandgap perovskite is Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 )3 + 5 mol% MACl + 3 mol% PbCl2. The required materials and masses are as follows: methylammonium chloride (4.7 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidinium iodide (187.8 mg), and lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent with a volume ratio of 3:1 to obtain a wide-bandgap perovskite precursor solution. Take 70 μL of the wide-bandgap perovskite precursor solution and drop it on the treated tin oxide substrate, and spin-coat it at a rotation speed of 5000 rpm for 20 s. 5 s before the end of the spin-coating program, quickly drop 100 μL of chlorobenzene on the center of the film. After the spin-coating program is completed, anneal it on a hot plate at 100 °C for 30 min.

[0119] S4. Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it on the passivated perovskite surface, and spin-coat it at 4000 rpm for 30 s.

[0120] S5. Deposit 70 nm thick gold as the electrode by vacuum thermal evaporation to obtain a perovskite solar electrode.

[0121] Detect the performance of the perovskite solar cells prepared by the methods of Examples 1-9 and Comparative Examples 1-3. Among them, the photocurrent density-voltage curve of the solar cell is obtained under the AM 1.5G illumination (100 mW / cm 2 ) emitted by the Oriel 91192 solar simulator of the American Keithley Instrments Company 2400 digital source meter, and the performance data shown in Table 1 are calculated accordingly.

[0122] Table 1

[0123]

[0124]

[0125] From the data in the table and Figures 1 to 3 the comparison chart, it can be seen that the conversion efficiency and open-circuit voltage of the perovskite solar cells prepared by the methods of Examples 1-8 are higher than those of Comparative Examples 1-3, which proves that the double-layer passivation process of the present invention plays a role in reducing the open-circuit voltage loss of the wide-bandgap perovskite, and improves the open-circuit voltage and conversion efficiency of the perovskite solar cells. At the same time, by comparing the detection data in the examples of the present invention with those in Comparative Examples 1 and 2, it can be known that the open-circuit voltage and conversion efficiency of the perovskite solar cells prepared after removing any one of the passivation layers are lower than those of the perovskite solar cells prepared in the examples of the present invention, which proves that there is a synergistic promotion technical effect between the two passivation layers.

[0126] Finally, it should be noted that: The above-described specific embodiments have further elaborated on the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above is only the specific embodiment of the present invention and is not used to limit the protection scope of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention. For those skilled in the art, it is obvious that this application is not limited to the details of the above-described exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or basic characteristics of this application. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting. The scope of this application is defined by the appended claims rather than the above description. Therefore, it is intended to encompass all changes falling within the meaning and scope of the equivalent elements of the claims in this application.

Claims

1. A wide bandgap perovskite solar cell, characterized in that: including a wide bandgap perovskite layer and a double passivation layer; The double passivation layer is located above the wide bandgap perovskite layer; The double passivation layer includes poly (2-ethyl-2-oxazoline) and phenylethylamine salt.

2. The wide bandgap perovskite solar cell according to claim 1, characterized in that: The structure of the phenethylamine salt is nR phenethylamine X, wherein n=1, 2 or 3, R is F, Cl, Br, CH3 or OCH3, and X is I, Br or Cl.

3. The wide bandgap perovskite solar cell according to claim 1, characterized in that: From bottom to top, it includes a conductive glass substrate, an electron transport layer, a wide bandgap perovskite layer, a double passivation layer, a hole transport layer, and a metal electrode.

4. The wide bandgap perovskite solar cell according to claim 3, characterized in that: The conductive glass substrate includes at least one of FTO glass and ITO glass; the electron transport layer includes at least one of SnO2, TiO2, and ZnO; the wide bandgap perovskite layer is composed of Cs x FA 1-x-y MA y Pb(I 1-z-w Br z Cl w )3, wherein 0.1≤x≤0.4, 0.02≤y≤0.05, 0.1≤z≤0.4, 0.02≤w≤0.05, and the bandgap width of the wide bandgap perovskite layer is 1.65-1.90 eV; the hole transport layer includes Spiro-OMeTAD, PTAA, NiO x At least one of; the metal electrode includes at least one of gold, silver, copper, and aluminum.

5. A method for preparing a wide bandgap perovskite solar cell according to any one of claims 1 to 4, characterized in that: The following steps are involved: A double passivation layer is deposited on the surface of the wide bandgap perovskite layer.

6. The preparation method according to claim 5, characterized in that: The method for depositing a double passivation layer on the surface of a wide bandgap perovskite layer comprises: A chlorobenzene solution containing poly(2-ethyl-2-oxazoline) is coated on the surface of the wide bandgap perovskite layer, followed by annealing; After annealing, an isopropanol solution containing phenylethylamine salt is applied.

7. The preparation method according to claim 6, characterized in that: The concentration of the poly(2-ethyl-2-oxazoline) is 0.01 mg / mL to 1 mg / mL, and the concentration of the phenethylamine salt is 0.1 mg / mL to 10 mg / mL.

8. The preparation method according to claim 6, characterized in that: The coating method comprises a spin coating method, wherein the rotation speed of the spin coating method is 1000 rpm to 4000 rpm when coating a chlorobenzene solution containing poly(2-ethyl-2-oxazoline); and the rotation speed of the spin coating method is 4000 rpm to 6000 rpm when coating an isopropanol solution containing phenylethylamine salt.

9. The preparation method according to claim 7, characterized in that: The temperature during the annealing treatment is 60°C to 120°C.

10. The preparation method according to claim 7, characterized in that: The annealing treatment time is 0 to 15 minutes.